Hormonal therapies up-regulate MANF and overcome female susceptibility to immune checkpoint inhibitor myocarditis - Zhang, Yaohua; Sun, Chengcao; Li, Yajuan; Qin, Juan; Amancherla, Kaushik; Jing, Ying; Hu, Qingsong; Liang, Ke; Zhang, Zhao; Ye, Youqiong; Huang, Lisa A.; Nguyen, Tina K.; et al. (Science translational medicine, 2022)
Immune checkpoint inhibitors (ICIs) have been increasingly used in combination for cancer treatment but are associated with myocarditis. Here, we report that tumor-bearing mice exhibited response to treatment with combinatorial anti-programmed cell death 1 and anti-cytotoxic T lymphocyte antigen-4 antibodies but also presented with cardiovascular toxicities observed clinically with ICI therapy, including myocarditis and arrhythmia. Female mice were preferentially affected with myocarditis compared to male mice, consistent with a previously described genetic model of ICI myocarditis and emerging clinical data. Mechanistically, myocardial tissue from ICI-treated mice, the genetic mouse model, and human heart tissue from affected patients with ICI myocarditis all exhibited down-regulation of MANF (mesencephalic astrocyte-derived neurotrophic factor) and HSPA5 (heat shock 70-kDa protein 5) in the heart; this down-regulation was particularly notable in female mice. ICI myocarditis was amplified by heart-specific genetic deletion of mouse Manf and was attenuated by administration of recombinant MANF protein, suggesting a causal role. Ironically, both MANF and HSPA5 were transcriptionally induced by liganded estrogen receptor beta and inhibited by androgen receptor. However, ICI treatment reduced serum estradiol concentration to a greater extent in female compared to male mice. Treatment with an estrogen receptor beta-specific agonist and androgen depletion therapy attenuated ICI-associated cardiac effects. Together, our data suggest that ICI treatment inhibits estradiol-dependent expression of MANF/HSPA5 in the heart, curtailing the cardiomyocyte response to immune injury. This endocrine-cardiac-immune pathway offers new insights into the mechanisms of sex differences in cardiac disease and may offer treatment strategies for ICI myocarditis.
Gesehen am 25.01.2024